Isolation and optimization of Bacillus thuringiensis BRB-3 isolated from germinated black upland rice seeds for GABA production - Rungnapha Wannasutta; Sophon Boonlue; Nuntavun Riddech; Wiyada Mongkolthanaruk (Heliyon)
Gamma-aminobutyric acid (GABA) is a non-coded amino acid that recently gained increased attention within the functional food industry. This study aimed to isolate endophytic bacteria from sterilized surfaces of germinated black upland rice seeds for GABA production and optimization. A total of 38 isolates were screened for glutamic acid decarboxylase (GAD) activity using a colorimetric method. Among these, thirteen isolates exhibited positive GAD activity. The BRB-3 strain emerged as the most promising, producing the highest GABA levels (4.54 g/L) at an optimal pH of 6.5. However, the BRB-3 strain was sensitive to pH lower than 5.5; so the pH was adjusted to 6.5 through all experiments. Further identification of the BRB-3 strain was performed using 16S rRNA gene sequence, which placed it in Bacillus cereus group. Subsequent rpoB gene sequence analysis confirmed that the BRB-3 strain was Bacillus thuringiensis BRB-3. GABA production was optimized in MRS broth by investigating carbon, nitrogen, monosodium glutamate (MSG), pH and temperature. Interestingly, the concentration of MSG did not impact GABA production of B. thuringiensis BRB-3. Under optimal conditions of 3 % soy protein as the nitrogen source, 2 % sucrose, no added MSG at 30 °C, pH 6.5 for 12 days, B. thuringiensis BRB-3 achieved a high GABA yield of 25.06 g/L (242.9 mM). Therefore, B. thuringiensis BRB-3 demonstrated significant potential for GABA production and could be utilized in various functional food products, including germinated rice seeds.